An Emperical Study on the Predictors of the Perceived Quality of Learning at Institutions of Higher Education 2D Model Approach - Mmatlou Matlakala; Norman Chiliya; Tinashe Chuchu; Tinashe Ndoro (My University, 2019)
The purpose of the present study was to conduct an empirical investigation into the predictors of the perceived quality of learning at institutions of higher education from the student’s perspective. The research was based on a conceptual model consisting of six proposed hypotheses. A quantitative study that utilised the survey methodology was adopted is it was imperative to obtain objective findings that would be later used for statistical purposes. In terms of selection of suit-able participants for the study, non-probability sampling, a form of convenience sampling was adopted. Perceptions of students regarding the quality of education were tested empirically. The 2 D Model approach was adopted to investigate this phenomenon. Data was collected from a total of 300 students from a selected university in South Africa. To analyse the data SPSS 24 and AMOS 24 were utilised for descriptive statistics and hypotheses testing respectively. A university’s reputation and the geographic region a student originated from were observed as having the greatest influence on those students’ perception of quality of education that a higher education institution provided.
Keywords: 2D model